Effect of different shielding conditions, thermal cycles and post- deposition treatments on melting behaviour and mechanical properties of additively built components - Cabellero Ramos, Armando Enrique (Cranfield University, 2023)
Additive manufacturing (AM) offers many advantages as compared to traditional manufacturing routes such as machining and forging thanks to its capability of reducing lead times, enhanced design flexibility and material saving. However, many challenges still must be overcome before this relatively novel technology can be implemented in the production of critical components. It is known that to achieve satisfactory performance of additively built parts it is important to ensure the absence of volumetric defects such as pores and the presence of a suitable microstructure that will offer the required mechanical properties. Many process variables such as shielding gas composition, thermal histories and post- deposition heat treatments can control these aspects. This work, focuses on the role of shielding gas composition on melting behaviour during laser powder bed fusion and on the microstructural evolution of stainless steel and the effect of different thermal cycles on two age hardenable alloys during Wire and Arc Additive Manufacture deposition. The objective of this thesis was to investigate how critical these variables can be in achieving the desired properties of 3D- printed parts for specific processes and alloys. The material interaction with the AM heat source is a complex phenomenon and for this reason, a wide range of advanced characterisation techniques were used in this work including high- speed imaging, scanning electron microscopy, chemical analysis, fractography, electron back-scattered diffraction, among others. It was possible to conclude that shielding gas composition is key to ensuring stability during laser powder melting of stainless steel. Additionally, the sensitivity of the microstructural features to different thermal cycles inherent to the Wire and Arc Additive Manufacture (WAAM) process was established for two age-hardenable alloys, 17-4PH (martensitic stainless steel) and Ti-5553 (near β titanium alloy). The effectiveness of standard post-deposition heat treatments to optimise the final mechanical properties of these two alloys was also identified. Finally, it was also possible to find how sensitive the developed microstructure of WAAM Ti-6Al-4V is to different levels of interstitial elements concentration. This is of great use for further applications as the incorporation of oxygen and its potential adverse effect on mechanical performance remains one of the main concerns for the processing of titanium alloys.
Keywords: Laser powder bed fusion; 17-4PH; Ti-5553; Wire and Arc Additive Manufacture; Ti-6Al-4V; additive manufacturing